Payment Banks : A New Mechanism To Promote Financial Inclusion (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Financial inclusion is one of the great initiated taken V. Venugopal  Reddy, the governor of RBI in April 2015 in his annual policy  statement and regarded technology adoption as an important  and essential feature for attaining financial inclusion. Financial  inclusion refers to providing financial services at affordable costs  to vast sections of disadvantaged and low income groups. The  payment banks, also known as niche banks, are the financial  entities established by the RBI in November 2014. These entities  can accept the deposits from the customer only upto Rs. 1 lakh  and pay interest on the same. These banks are not allowed to  lend money on credit to its customers and external parties as  well as not allowed to issue plastic money i.e. debit and credit  cards. The main objective behind setting up of payment banks  is to support the scheme of financial inclusion by offering small  saving accounts and payment or remittance services to low  income household, small businesses and other unorganized sector  entities. This research paper attempts to analyze whether the role  played by these payment banks established by RBI is sufficient in  strengthening the campaign of financial inclusion in India.
Keywords: Financial Inclusion; Payment Banks; customers; Financial services; Technology adoption